ENHANCING COMPETENCIES OF CONTACT CENTER TEAM LEADERS THROUGH BLENDED LEARNING: EVIDENCE FROM A NATIONAL COMPETITION IN INDONESIA - Andi Anugrah; Mochammad Sukardjo; Khaerudin (Improvement: Jurnal Ilmiah untuk Peningkatan Mutu Manajemen Pendidikan, 2025)
This study aims to analyze the competency development needs of contact center team leaders based on the evaluation of training and implementation during the Indonesian National Contact Center Competition. A total of 416 participants from various inbound, outbound, and digital positions took part in the program, including 54 Team Leaders. The competency assessment was conducted using a computer-based testing application to ensure measurable and objective results. Participants were prepared through two different approaches: the first group combined e-learning with video conferencing, while the second group combined e-learning with face-to-face sessions. Data analysis focused specifically on team leader participants and applied ANOVA to examine differences in learning outcomes between groups, as well as to identify critical areas requiring competency enhancement. The findings revealed significant differences between the two groups and highlighted the need for strengthening competencies in quality measurement, case analysis, data analysis, performance evaluation, and the strategic role of the contact center. These results emphasize the importance of targeted training for team leaders to enhance their ability to manage contact center operations. The use of blended learning methods combined with computer-based testing provides a more accurate depiction of training effectiveness.